2017
DOI: 10.1016/j.rboe.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The use of tranexamic acid in patients submitted to primary total hip arthroplasty: an evaluation of its impact in different administration protocols

Abstract: ObjectivesThere is still no consensus as to the best form and dosages of use of tranexamic acid. The aim of this study was to evaluate the use of tranexamic acid in total hip arthroplasty, in order to reduce blood loss and decrease hemoglobin, taking into account different administration protocols.Methods42 patients submitted to total hip arthroplasty were divided into three groups. The study was prospective and randomized. Group 1 received a venous dose of tranexamic acid of 15 mg/kg, 20 min prior to bolus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…As for the different administration protocols, the use of the bolus and bolus/infusion pump methods has shown to have a very similar influence on serum hemoglobin and the amount of blood loss through the suction drains, showing no statistically significant differences. 15…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the different administration protocols, the use of the bolus and bolus/infusion pump methods has shown to have a very similar influence on serum hemoglobin and the amount of blood loss through the suction drains, showing no statistically significant differences. 15…”
Section: Discussionmentioning
confidence: 99%
“…As for the different administration protocols, the use of the bolus and bolus/infusion pump methods has shown to have a very similar influence on serum hemoglobin and the amount of blood loss through the suction drains, showing no statistically significant differences. 15 A Cochrane review showed that, in an emergency surgical setting, TXA reduced the likelihood of receiving an erythrocyte transfusion by 30%. 14…”
Section: Tranexamic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Total hip arthroplasty (THA) has become an excellent treatment method for pain relief and functional improvement in patients with degenerative hip joint disease. Osteoarthritis (OA) is one of the most common chronic conditions, particularly in elderly populations, which leads to pain and loss of function [1,2] . Total hip arthroplasty (THA) is a surgical intervention that is carried out in end-stage arthritis patients.…”
Section: Introductionmentioning
confidence: 99%
“…They included only randomized studies and reported that the use of multiple dose regimens produced a profound risk reduction in need for transfusion. Melo et al 22 divided 42 patients into three dosing groups as follows: (1) noTXA, (2) one 15 mg/kg IV bolus 20 minutes before incision, and (3) the same bolus dose as group two with the addition of a 10 mg/kg by infusion pump for the duration of the procedure. They observed the TXA groups to be superior to the control group in terms of hemoglobin drop and need for transfusion, with no difference between the TXA dosing regimens.…”
mentioning
confidence: 99%